Variation in Nutritional and Antioxidant Attributes of Moringa oleifera L. Leaves at Different Maturity Stages - Qadir, Rahman; Anwar, Farooq; Bashir, Kiran; Tahir, Mudassir Hussain; Alhumade, Hesham; Mehmood, Tahir (Frontiers in Energy Research, 2022)
The present work reveals variation in the nutritional and antioxidant profiles of Moringaoleifera leaves with regard to four maturity stages (early, mid, penultimate and late). The corresponding yield of 80% methanolic extract (14.21 and 9.69%) and total phenolic contents (TPC) of the extract (95.26 and 38.22 mg GAE/g) from M. oleifera leaves were found to be maximum at early stage and minimum at the later stage. Total flavonoids, ash, protein, vitamin C and β-carotene contents were found to be minimum at the early stage and maximum at later stage (12.26 ± 0.47 to 30.07 ± 1.09 mg/g, 10.36–15.92%,50.3 ± 0.15 to 56 ± 0.77 mg/100 g, 143.14 ± 0.74 to 164.81 ± 0.44 mg/100g, and 89 ± 0.28 to 112.8 ± 1.40 mg/100 g). Amino acids including valine, alanine, leucine and phenylalanine were identified with their least contents at early stages (90.87, 53.07, 55.21, and 48.65 µg/g) and maximum at later stages (197.66, 114.3, 114.2, and 104.5 µg/g, respectively). The levels of different minerals such as Cu, Fe, Mn in M. oleifera leaves at different maturity stages varied from 0.59 to 2.08, 21.96 to 58.68, and 5.56 to 13.84 mg/100 g, respectively. RP-HPLC analysis of the nutritionally rich later-stage leave samples revealed the presence of quercetin as a major component (21.64 mg/kg), followed by benzoic acid, ferulic acid, sinapic acid, gallic acid, and p-coumaric acid with contributions of 13.03, 8.85, 3.39, 2.88, and 1.59 mg/kg, respectively. Overall, a considerable variation in the profile of different nutrients and antioxidants was noted in M. oleifera leaves as maturity progressed. These results support the harvesting of M. oleifera leaves at an appropriate maturity stage to maximize the functional food and nutraceutical benefits of this valuable food commodity.